Using digital technology to enhance adolescent and young adult development: An examination of implications for child welfare in Nigeria - Abiola Adiat Omokhabi (Universitas Trunojoyo Madura, 2023)
The use of digital devices is increasing among adolescents and young adults (AYAs), who consider them an important part of their daily lives. This study investigated the use of digital technology by AYAs in Oyo State, Nigeria. A quantitative research design was adopted and AYAs between the ages of 13 and 18 who use smartphones were recruited from public secondary schools in Ibadan metropolis; Ibadan North, Ibadan North-East, Ibadan North-West, Ibadan South-East and Ibadan South-West areas. The probability and nonprobability sampling techniques were used to select 159 respondents. The results showed that digital technology have some roles on AYAs behaviors. AYAs perceived the risk factors as eye strain, sleep problems when using digital technology for many hours in a day, poor posture, reduced physical activity, to name a few. AYAs’ perceptions of parents/guardians protecting them from the Internet safety risks show that their parents/guardians do not talk to them about online content and behavior, and do not use controls or other methods of blocking, filtering, or monitoring their online activities. Based on the results, it has been recommended that digital safety should be included in the curriculum of some secondary school subjects, such as computer science.